PENGARUH TINGKAT KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN HOTEL MJ SAMARINDA - Eka Yudhyani, Mariana Herwin, H. Eddy Segiarto, (EKONOMIA, 2016)
In this research Issue is the declining level of sales and net profit at PT Timah (Persero) TBk so need to look for causes of the decrease in the level of profitability of the company.The basic theory is the theory of financial management supporting profitability. The hypothesis of this research is